Avaliação do plano de gerenciamento de resíduos de serviços de saúde aplicando as boas práticas de Avaliação Ambiental Estratégica (AAE): uma proposta de melhoria por meio do planejamento estratégico - Campos, Fernanda Julio Barbosa (2015)
The Strategic Environmental Assessment (SEA) is a tool to support the environmental assessment planning established by European Directive, DIRECTIVE 2001/42 / EC in order to increase environmental protection and the integration of the environment in the Plans, Programs and Projects (PPP´s). Currently, in addition to the European Community, countries like Canada, and even Brazil have used SEA, so that the strategic actions developed in PPP's have long-term scope and aim at sustainable development. The National Solid Waste Policy (NSWP) of Brazil, created by Law nº13205 of 2010, sets the guidelines for the integrated management and solid waste management. Resulting from this NSWP arise instruments it instituted among which the Solid Waste Management Plans (SWMP). Resolution of the Board of Directors (DRC) of the National Health Surveillance Agency (NHSA) No 306 of 7 December 2004 states that the waste generators of health services in operation or to be deployed, prepare and deploy Health Plan Services Waste Management (HPSWM), according to the current legislation, especially the standards of health monitoring. The implementation of HPSWM is a challenge for health facilities and waste when improperly managed risky to health and the environment. As the SEA a support tool for planning, the aim of this study was to propose strategic actions based on best practices of SEA to complement existing shares in Strategic Planning (SP) of the studied public hospital to reflect the HPSWM, increasing protection environmental and integration of the environment with the development plan. This research is supported in the descriptive qualitative and the main method used was the action research. Through literature review, document analysis, file records, semi-structured interviews and direct observation were described the preparation of HPSWM and SP procedures, the diagnosis of HPSWM process was carried out and then the HPSWM was compared to the criteria of good practice of SEA. The result was the completion of strategic actions provided by SEA to prepare the HPSWM. The main contribution of this thesis, it is understood to be the fact that SEA can be inserted in the Strategic Plan of the institutions as an aid instrument for action planning of development plans of Health Services Waste Management, to increase protection to the environment.